Lyndon B. Johnson papers - Johnson, Lyndon B. (Lyndon Baines), 1908-1973.
Miscellaneous papers of or relating to Johnson. Includes a letter relating to his membership in the Masons, a letter and resolution addressed to Lady Bird Johnson, material relating to the 1966 Johnson-Nugent wedding, a copy of Johnson's remarks at a Carl Sandburg memorial service, memorabilia relating to White House social functions and programs, and photographs.
Chiefly photocopies of material in private hands.
Private
U.S. president and vice-president and U.S. senator and representative from Texas.
Keywords: Johnson, Lady Bird, -- 1912-2007 -- Correspondence; Nugent, Luci Baines Johnson; Nugent, Patrick John, -- 1943-; Sandburg, Carl, -- 1878-1967.; White House (Washington, D.C.); Freemasonry; Washington (D.C.) -- Social life and customs; Presidents -- United States; Representatives, U.S. Congress -- Texas; Senators, U.S. Congress -- Texas; Vice-Presidents -- United States